PENATALAKSANAAN FISIOTERAPI PADA KASUS OSTEOARHTRITIS GENU DEXTRA DENGAN METODE KINESIOTAPPING, HOLD RELAX STREATCHING DAN MODALITAS US - Salshabila Adinda Yuri; Putra Hadi; Faridah Faridah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
ABSTRACT Background : Osteoarhthritis (OA) one of the pathic conditions often seen in the elderly. Among the causes of musculoskeletal disorders and the most common joint degenerative disorder, caused by disease in the elderly is chronic pain in the joints, the problems in osteoarhtrifits of the knee are complex because of abrasion of the joints and the formation of new bones. Degenerative encasement on the knee can cause the surface of the knee joint to become irregular and violent, inm will cause pain and swelling in the knee. The study aims to find out the results of the methods of kinesiotapping, hold relaxing streatching and modality us phonoporesis in reducing pain, increasing the muscle strength and range of joints (LGS) in cases of osteoarhthritis. The method used was case study method with one person in question using a vase to measure pain, MMT to measure muscle strength and a goneometer to measure LGS. The result of studies conducted in a new city district, the jambi city is the method of kinesiotapping, hold relax streatching, the modality of us phonoporesis during 3 weeks of therapy that can reduce pain, increasing muscle strength and joints (LGS) patients osteoarhthritis. The conclusion of the study is that phonoporesis dapa reduce pain, kinesiotapping has not been able to increase muscle strength and hold relaxing streatching increasing the LGS of osteoarhthritis patients because interventions have been performed that can enhance the strength of muscle and the irrational muscle resilience of the legs, when the essential muscle has been strong fascia plantar is not working hard and promote inflammation of the plantar fascia and can promote functional activities.